Functional traits of trees on and off termite mounds: understanding the origin of biotically‐driven heterogeneity in savannas. (31st August 2012) - Van der, F.; Howison, R.; Reinders, J.; Fokkema, W.; Olff, H.; Bruun, Hans Henrik
Abstract Questions In African savannas, Macrotermes termites contribute to small‐scale heterogeneity by constructing large mounds. Operating as islands of high nutrient and water availability and low fire frequency, these mounds support distinct, diverse communities of trees that have been shown to be highly attractive to browsers. However, the distinct traits of tree species on termite mounds have hardly been studied, even though this may help to understand processes determining (1) their characteristic community structure and (2) attractiveness for browsers. Here, we compare functional trait and browser preference values between tree species on and off termite mounds. Location Hluhluwe‐iMfolozi Park, Kwazulu‐Natal, South Africa. Methods We recorded tree community compositions for 16 large Macrotermes natalensis mounds and 16 control plots of 100 m2 each in a paired design. For each observed tree species we measured 22 traits, related to water and nutrient use, fire tolerance, light competition and anti‐herbivore defence, and compared average trait values between mound and control communities. Furthermore, we investigated the feeding preferences of ungulate browsers for the most common tree species and how this was linked to their associated traits. Results Termite mounds supported tree communities that were distinct from the surrounding savanna vegetation. Mounds hosted more evergreen and less leguminous tree species than control communities, and the dominant species were less mechanically defended, less nutritious, had larger leaves and lower wood density than the species dominating control plots. Browsers preferred leguminous tree species with high leaf N and P content, which were relatively rare on termite mounds. Conclusions Overall, we conclude that termite mounds in this savanna form small refuges for tree species that seem less adapted to fire (more evergreens), have low nutrient availability (less nitrogen fixers) and suffer from water stress (larger leaf sizes) than typical savanna trees. Surprisingly, despite their reputation as browsing hotspots, the tree species dominating mounds are less nutritious and less preferred by browsers than tree species of the surrounding savanna, which may be explained by the relatively nutrient‐rich nature of this savanna or intraspecific trait differences.